1994
DOI: 10.1080/1066892940180204
|View full text |Cite
|
Sign up to set email alerts
|

Effective Strategies for Enhancing Minority Faculty Recruitment

Abstract: The results of two surveys of 1,387 two-year college administrators reveal that attitudinaf and structural barriers need to be removed before improvements can be made in the percentage of minority full-time faculty at community colleges.A recent study reveals that two-year colleges report enrolling a disproportionately large number of minority students, while minority representation among full-time faculty members remains low. In this study, institutional data on the numbers of minority full-time, two-year col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…This study, which was based on an extensive review of the recruitment literature and considered both the private and education sectors, was an initial exploration of personal characteristics in the community college recruitment context. Findings from this research are important in light of the well-documented wave of retirements occurring among community college faculty members (Gibson-Benninger & Ratcliff, 1996;Higgins et al, 1994;Lawhon & Ennis, 1995;Miller, 1997;Opp & Smith, 1994;Schuster, 1995). Knowing which personal characteristics are associated with applicant attraction to position vacancies can aid recruiters in better targeting pools of potential applicants.…”
Section: Onclusionmentioning
confidence: 90%
See 1 more Smart Citation
“…This study, which was based on an extensive review of the recruitment literature and considered both the private and education sectors, was an initial exploration of personal characteristics in the community college recruitment context. Findings from this research are important in light of the well-documented wave of retirements occurring among community college faculty members (Gibson-Benninger & Ratcliff, 1996;Higgins et al, 1994;Lawhon & Ennis, 1995;Miller, 1997;Opp & Smith, 1994;Schuster, 1995). Knowing which personal characteristics are associated with applicant attraction to position vacancies can aid recruiters in better targeting pools of potential applicants.…”
Section: Onclusionmentioning
confidence: 90%
“…Kaplowitz (1986) summarized the importance of faculty recruitment to the success Finally, empirical research about community college faculty recruitment is essential at this time because ''as the children of the baby boomers reach college age, an enrollment surge is inevitable, [and] at the same time, large numbers of faculty will approach retirement'' (Miller, 1997, p. 84). This potential shortfall of quali ed community college faculty members has been well documented (Gibson-Benninger & Ratcliff, 1996;Higgins, Hawthorne, Cape, & Bell, 1994;Lawhon & Ennis, 1995;O'Banion, 1994;Opp & Smith, 1994;Schuster, 1995).…”
mentioning
confidence: 99%
“…We found that seven articles published in the journal from 1990 to 2000 focused directly on indirectly on Latinos (Ackermann, 1991;Bonham & Luckie, 1993;Brazziel & Brazziel, 1994;Castellanos & Fujitsubo, 1997;Opp & Smith, 1994;Starrfield, 1992;Vazquez & Garcia-Vazquez, 1998. ) Of these, only two directly concerned Latinos (Castellanos & Fujitsubo, 1997;Vazquez & Garcia-Vazquez, 1998).…”
mentioning
confidence: 86%
“…Opp & Smith (1994) surveyed academic vice presidents at community colleges to gather data on the number of full time faculty from underrepresented populations. Opp & Smith (1994) surveyed academic vice presidents at community colleges to gather data on the number of full time faculty from underrepresented populations.…”
Section: Research With Faculty Participantsmentioning
confidence: 99%
“…The emphasis of their approaches has been to build stronger institutional commitment to diversity, more involvement of faculty in diversity issues, increased support for minority scholars, and use of opportunity hires and incentives (Light 1994;Opp and Smith 1994;Smith et al 2004;Turner 2002). Our intention in this study was to examine the Korean government's policy approach, the PWFI.…”
Section: Purpose and Research Questionsmentioning
confidence: 99%